Peran Keteladanan Orang Tua dalam Pembiasaan Ibadah Bagi Anak Usia 4-6 Tahun - Agus Ruswandi; Avirda Nuri Quroini Avirda; Ghina Fauziyyah Mar’atus Shalihah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The aim of the study was to instill the practice of prayer in children and introduce them to Islam through the practices of their parents from an early age. Qualitative research methods were chosen, especially descriptive qualitative research. The study, conducted at TK Al Amanah, included five parents with children aged 4 to 6. The findings highlighted the significant role parents play in habituating worship in children within this age group. Leading by example proved to be influential in motivating and encouraging children to engage in worship activities, such as prayer, recitation, and supplication. Consistent and continuous parental guidance in worship had a positive impact on shaping children's moral and spiritual character. Effective communication and a gentle approach from parents also contributed positively to worship habituation. Furthermore, the study emphasized the influence of the environment on children's worship activities, as a comfortable setting facilitated familiarity and regularity in daily worship practices.